Hubungan Status Ekonomi Orang Tua dengan Depresi pada Remaja di SMA N 8 Surakarta - Noviana Rahmawati; . Machmuroch; . Suparman (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Depression in adolescents due to increased life that full of stress (pressure) and demands are not fulfilled when solving problems. It can be caused by various factors, such as self-pressure, outside pressure, problems with friends, and also economic of family issues. Socioeconomic status relate to physical and mental health of adolescents. This study aims to determine the relationship of the economic status of parents with depression in adolescents at SMA N 8 Surakarta. Methods: This study is a correlational study with cross sectional approach held from October to November 2013 in the SMAN 8 Surakarta. A total of 94 studens were taken by simple random sampling method. Subject was asked to fill out the form identity, informed consent and questionnaires. Then the results of the questionnaire were tested by Contingency coefficient through SPSS 17.0 for Windows. Results: The samples used were 94 students. A total of 64 students (68.1%) have parents with high economic status. The rest as many as 30 students (31.9%) have parents with low economic status. Distribution of depression showed 39.4% of students have mild depression, 31.9% of students have middle depression, the remaining 28.7% of students have severe depression. The cross distribution of these two variables showed that students with a low economic status were more severely depressed, while students with high economic status were less severely depressed. Contingency coefficient (C) statistical test of 0.248 indicates that the degree of closeness of the relationship between the two variables is weak. Conclusions: There is a relationship of economic status with the incidence of depression in adolescents at SMAN 8 Surakarta with the level of relationship between the two variables is weak. Keywords: Economic Status, Adolescents, Depression